Public perception of climate engineering and carbon capture and storage in Germany: Survey evidence - Carola Braun; Christine Merk; Gert Pönitzsch; Katrin Rehdanz; Ulrich Schmidt (Climate Policy, 2018)
Climate engineering (CE) and carbon capture and storage are controversial options for addressing climate change. This study compares public perception in Germany of three specific measures: Solar radiation management (SRM) via stratospheric sulphate injection, large-scale afforestation, and carbon capture and storage sub-seabed (CCS-S). In a survey experiment we find that afforestation is most readily accepted as a measure for addressing climate change, followed by CCS-S and lastly SRM, which is widely rejected. Providing additional information decreases acceptance for all measures, but their ranking remains unchanged. The acceptance of all three measures is especially influenced by the perceived seriousness of climate change and by trust in institutions. Also, respondents dislike the measures more if they perceive them as a way of shirking responsibility for emissions or as an unconscionable manipulation of nature. Women react more negatively to information than men, while the level of education or the degree of intuitive vs. reflective decision-making does not influence the reaction to information.
Keywords: 330; climate engineering; solar radiation management; carbon capture and storage; climate change; public opinion; information